PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA, DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN (Studi Empiris pada Konsumen CV. Tiara Sakti Semarang) - Ria Arnisya Handayani, 08.05.51.0050; Rizal, Alimuddin (Students Journal of Economic and Management, 2014)
This study takes an object on CV. Tiara Sakti Semarang is one company that is engaged in services, especially services airfares. The research aims to analyze the effect of service quality, price perceptions and beliefs towards customer satisfaction. Total sample of 99 respondents. Sampling technique in this study using purposive sampling criteria are based sampling that consumers who use the services or product of CV. Tiara Sakti at least 2 times already and are willing to be the respondent at the time of questionnaire distribution. The test results are obtained by partial positive and significant effect between service quality on customer satisfaction, there is a partial positive and significant effect between price perception and customer satisfaction are partially positive and significant effect of trust on customer satisfaction. Keywords: quality of service, price perceptions, beliefs, and customer satisfaction